2014
DOI: 10.14411/eje.2014.007
|View full text |Cite
|
Sign up to set email alerts
|

Ground spider assemblages (Araneae: Gnaphosidae) along an urban-rural gradient in the city of Heraklion, Greece

Abstract: Abstract. The responses of gnaphosid spiders to an urbanization gradient (urban-suburban-rural areas) were studied using pitfall traps in and near the city of Heraklion, in Crete, Greece, from October 2010 to October 2011. Our results indicate that richness and abundance of species of spiders decreased from the rural area to the center of the city, but not significantly so. Temporal beta diversity was significantly higher in urban areas, which indicates a high temporal variability in species composition of gna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…The effect of urbanization is generally more evident in the core of a city, which is surrounded by areas of decreasing habitation and development with moderate or low disturbance levels (Kaltsas et al 2014). Still, our results indicate that urbanization does not have a negative effect on crab spider species richness, at least in green spaces ≥ 1 ha, which is partly consistent with several studies showing higher spider richness in urban green spaces compared to less disturbed habitats such as Philpott et al (2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The effect of urbanization is generally more evident in the core of a city, which is surrounded by areas of decreasing habitation and development with moderate or low disturbance levels (Kaltsas et al 2014). Still, our results indicate that urbanization does not have a negative effect on crab spider species richness, at least in green spaces ≥ 1 ha, which is partly consistent with several studies showing higher spider richness in urban green spaces compared to less disturbed habitats such as Philpott et al (2014).…”
Section: Discussionsupporting
confidence: 90%
“…In Debrecen, Hungary, they found that forest species were significantly affected by urbanization, while the populations of other generalist species increased in more disturbed patches. In Heraklion, Greece, Kaltsas et al (2014) also observed an overall negative Does urbanization have positive or negative effects on Crab spider diversity?…”
Section: Discussionmentioning
confidence: 97%
“…The habitat loss due to urbanization and the intensity of management of the greeneries results in a specific community assemblage in all groups of arthropods. As it has been mentioned above, the type of management can particularly affect the survival chances of the large number of stenotopic and oligotopic species (Mabelis 2005;Antonova and Penev 2008;Magura et al 2008;Duffey 2010;Kaltsas et al 2014;Radchenko et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It covers an area of approximately 24 km 2 with an estimated population of 173,450 (according to the General Population Census 2011) at a density of 7,227 residents per square kilometer. Heraklion is mainly flat with several prominent hills, characterized by numerous floral species, mainly introduced, such as Hirschefeldia incana and Conyza albida (common species along the roadsides), Petromarula pinnata (endemic plant of Crete), Ailanthus altissima (dominant plant at the archaeological site of Knossos), Hyoscyamus aureus (common in the Venetian city walls) (for further habitat description see also Vogiatzakis and Rackham 2008 and Kaltsas et al 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, nine sampling sites were selected: i) three urban sites within the city of Heraklion, ii) three suburban sites on the boarders of the city, and iii) three rural sites in natural environment. The selection of the sampling sites was made on the basis of the similarity of vegetation and the percentage of built-up area ( Ishitani et al 2003 , Kaltsas et al 2014 ). Further details on the environment of each site can be found in Fig.…”
Section: Methodsmentioning
confidence: 99%